CONVENTIONAL BANK CONVERSION ANALYSIS TO SHARIA BANKS ACCORDING TO THE FINANCIAL SERVICES AUTHORITY REGULATION - nurhadi, nurhadi (Institut Pesantren KH Abdul Chalim Mojokerto, 2019)
Keywords: Analysis, Conversion,  Conventional Banks, Islamic Bank, Financial Fervices. Authority     OJK (financial services authority) that issues a rule about conventional banks can make changes to business activities into Islamic banks, but not vice versa. Changes must obtain permission and fulfill the requirements. After permission is obtained, it must clearly state the word